2020
DOI: 10.1002/adtp.202000001
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel‐Based Multifunctional Dressing Combining Magnetothermally Responsive Drug Delivery and Stem Cell Therapy for Enhanced Wound Healing

Abstract: Multifunctional dressings are attracting increased interest in the area of tissue engineering and regenerative medicine. Wound healing is a dynamic and complex process that requires multidisciplinary management. However, dressings that exhibit both anti‐infective and tissue regenerative properties are still limited. Herein, a hydrogel‐based multifunctional dressing weaved by drug‐loaded magnetothermally responsive [Fe3O4@SiO2‐interpenetrating polymer network (IPN)] microfibers and human umbilical cord mesenchy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 66 publications
0
10
0
Order By: Relevance
“…12f–h). 214 Owing to the magnetothermal heating effect of the embedded Fe 3 O 4 @SiO 2 , the hydrogel could effectively release loaded antibiotics on-demand to exert antibacterial effects under an external magnetic field (Fig. 12i and j).…”
Section: Mins In Different Biomedical Applicationsmentioning
confidence: 99%
“…12f–h). 214 Owing to the magnetothermal heating effect of the embedded Fe 3 O 4 @SiO 2 , the hydrogel could effectively release loaded antibiotics on-demand to exert antibacterial effects under an external magnetic field (Fig. 12i and j).…”
Section: Mins In Different Biomedical Applicationsmentioning
confidence: 99%
“…[95] In another study, a multifunctional dressing containing human umbilical cord mesenchymal stem cells (HUMSCs)laden microfibers was developed based on Fe 3 O 4 @SiO 2 -IPN microfibers. [96] Fe 3 O 4 @SiO 2 was inserted into magnetothermally responsive microfibers with a magnetothermal heating effect. The release of antibiotic drugs was related to temperature changes.…”
Section: Thermosensitive Multifunctional Hydrogel Dressings For Wound...mentioning
confidence: 99%
“…Furthermore, the hydrogel dressing absorbed the wound exudate, provided a moist environment, preserved the cells in the defected wound, and significantly facilitated wound healing. [96]…”
Section: Thermosensitive Multifunctional Hydrogel Dressings For Wound...mentioning
confidence: 99%
“…Zhang et al demonstrated the microfluidic-mediated generation of hydrogel dressing of drug-loaded magnetothermally responsive [Fe 3 O 4 @SiO 2 -interpenetrating polymer network (IPN)] microfibers compounded with human umbilical cord mesenchymal stem cells hUMSCs. 135 The core solution for the preparation of Fe 3 O 4 @SiO 2 -IPN microfibers consisted of sodium alginate, N -isopropylacrylamide (NIPAM), acrylamide (AAm), N , N -methylenebisacrylamide (BIS), ammonium persulfate (APS), and Fe 3 O 4 @SiO 2 nanoparticles, and the shell solution consisted of CaCl 2 and TEMED solution. The microfibers were then freeze-dried and immersed in ciprofloxacin hydrochloride solution for drug loading.…”
Section: Advances Of Microfluidic-based Functional Materials For Woun...mentioning
confidence: 99%